Planejamento estratégico: um método para implementação na micro e pequena empresa - Quadros, Juliane do Nascimento de (2013)
The marketing universe of micro and small enterprises is widely competitive, which will be absorbed those that have higher quality and competence. In the quest for excellence, enterprises resort to administrative tools that can help achieve your goals. When it comes to goals, strategic planning is used because the interpretation it makes of the environment, guiding and adapting the organization the most appropriate way to achieve them. However, the micro and small business almost does not use the technique and the main reason is the difficulty of implementing the method. Under this scenario, this research seeks to evaluate implementation models of strategic planning in order to design a suitable model to the reality of micro and small Brazilian company, enabling it to implement this management technique efficiently and effectively for these organizations. To design this study, we used quantitative, qualitative, exploratory and descriptive methods. As a qualitative, the case study was the appropriate methodology for validation of the model, it was implemented in a small business. And to analyze the relationship between the micro and small enterprise with strategic planning an interview was conducted with 28 companies of this size. The proposed method has met the main requirement of ease of deployment of strategic planning, for the company where it was applied, there was no difficulty or excessive time to complete the steps proposed, in addition, it contributed to the reduction of administrative problems in these companies, as lack delegation and the difficulty of evaluating their strategies.